Reduce the Influence of Horizontal and Vertical Cold Joints on the Behavior of High Strength Concrete Beam Casting in Hot Weather by Using Sugar Molasses - Hameed Naser Al-Mamoori, Fatimah; Hameed Naser Al-Mamoori, Ali (International Journal of Engineering and Technology, 2018)
The current research studies the effect of cold joints on the behavior shear and flexure of High Strength Concrete (HSC) beams caused by delayed casting sequence during the hot weather in summer of Iraq.Fresh concrete should be kept alive during the various casting batches for concrete element by re-vibration. However, the over vibration caused loss in homogeneity and it is difficult to keep the workability of concrete during hot weather due to the effect of setting time.To deal with this problem of improper casting sequence, which eventually leads to the formation of cold joints, it will be used sugar waste (named as Sugar Molasses (SM)) is a by-product resulted from refining process of sugar as a delayed agent to increase the setting time in order to prevent early set of concrete due to adverse effects in construction joint of hot weather.In the current study, the first objective aims to investigate some of fresh and hardened mechanical properties of HSC (with high cement content) using SM at percentages of (0, 0.05, 0.1, 0.2, 0.3) % from the weight of cement under the concept of sustainable development. The second objective aims to investigate the location and surface texture effect of horizontal and vertical cold joints on the flexural and shear behavior of beam with/without SM. This objective includes testing of twenty four plain concrete beam of (110Ã—110Ã—650 mm) under two point load; half of them casting without roughing (smooth) the old layer and the other casted after roughed it.SM content of 0.2% of cement weight can improve compressive strength by about 11.2% at 28 days and delay initial setting time by about 4.617 hours (277 minutes). No adverse effect on concrete have been observed at this dosage of SM concentration for the ages of concrete cylinders studied. Delays in the setting of concrete at this dosage of SM content help in reducing the early setting of concrete and therefore reduced the impact of the cold joints formation in concrete beams under Iraqi hot weather condition. The failure load for the beams with SM of smooth and rough vertical joints is in the range between (1.95 - 2.12) and (1.46-1.37); respectively times that of the case of beam without SM.Â